2016
DOI: 10.1371/journal.pone.0151746
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Phylogeography Reveals Cryptic Diversity and Repeated Patterns of Cladogenesis for Amphibians and Reptiles in Northwestern Ecuador

Abstract: Comparative phylogeography allow us to understand how shared historical circumstances have shaped the formation of lineages, by examining a broad spectrum of co-distributed populations of different taxa. However, these types of studies are scarce in the Neotropics, a region that is characterized by high diversity, complex geology, and poorly understood biogeography. Here, we investigate the diversification patterns of five lineages of amphibians and reptiles, co-distributed across the Choco and Andes ecoregion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
58
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 96 publications
6
58
0
3
Order By: Relevance
“…For instance, three river drainages separate the landscape, following the genetic clustering of our populations. The main river drainage composed of the Esmeraldas and Guayllabamba Rivers has been identified in the geographical pattern of differentiation in other frog species, such as Pristimantis nietoi and P. walkeri , populations of the snake Bothrops punctatus (Arteaga et al., 2016), and roughly separates the distribution range of O. sylvatica in two main groups (Figures 2 and 6). The northern genetic cluster (i.e., San Antonio, Lita, Alto Tambo, Durango, and Otokiki) and two populations from the southern genetic cluster (i.e., Felfa and Cristóbal Colón) are located north of Esmeraldas River, with the rest of the southern cluster (i.e., Simón Bolívar, Puerto Quito, Cube, Quingüe, Santo Domingo, and La Maná) in the south.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…For instance, three river drainages separate the landscape, following the genetic clustering of our populations. The main river drainage composed of the Esmeraldas and Guayllabamba Rivers has been identified in the geographical pattern of differentiation in other frog species, such as Pristimantis nietoi and P. walkeri , populations of the snake Bothrops punctatus (Arteaga et al., 2016), and roughly separates the distribution range of O. sylvatica in two main groups (Figures 2 and 6). The northern genetic cluster (i.e., San Antonio, Lita, Alto Tambo, Durango, and Otokiki) and two populations from the southern genetic cluster (i.e., Felfa and Cristóbal Colón) are located north of Esmeraldas River, with the rest of the southern cluster (i.e., Simón Bolívar, Puerto Quito, Cube, Quingüe, Santo Domingo, and La Maná) in the south.…”
Section: Discussionmentioning
confidence: 70%
“…(2016). They identified several geographical barriers to dispersion, especially river drainages, and their data suggests that diversification also follows thermal elevation gradients between the Chocoan region and the Andes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that sister species tend to segregate along environmental gradients suggesting ecological speciation and niche lability (Arteaga et al 2016; Graham et al 2004; Ron et al 2012). Other studies have shown that sister species tend to be allopatric but with similar environmental niches (Cadena et al 2012; Ortega-Andrade et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that other cryptic species of anoles from the Tropical Andes are yet to be discovered, as has been the case in other taxa (e.g. Guayasamin et al 2015; Arteaga et al 2016; Guayasamin et al 2017), and we highlight the importance of building modern specimen collections of supposedly known species (e.g., A.aequatorialis ), particularly from poorly explored areas. After extensive geographical sampling, we conclude that the new species described in this paper occurs only north of the Mira River Basin in northern Ecuador (Figure 13).…”
Section: Discussionmentioning
confidence: 63%